Fertility Behaviour among the Bote Women of Chitwan District, Nepal - Dhakal, Keshav Raj (The Third Pole: Journal of Geography Education, 2019)
This paper highlights on fertility behavior of Bote women by calculating the mean children ever born (CEB) focusing the case of Chitawan district. Fertility behavior helps to know about the factors that influence on child birth and indirectly to control population growth. Relevant data were obtained from both primary and secondary sources. Primary data were collected through interview and field observation. For this, a total of 48 newly married women of Bote community between the age of 15 and 49 years were purposefully selected and interviewed. The study showed that the average number of children ever born in the study area is found 2.64. In recent years, mean CEB has been increasing in this community with the increase in age of marriage and education. The CEB also varies by types of occupation. Women involved in diversified occupations have lower fertility rate as compared to women involved in non-diversified traditional occupations. Nowadays, with the increase in level of education, number of women using contraceptive has been increasing. However, still a large section of fertile aged women do not use such birth controlling measures. Awareness programs/campaigns for increasing education and use of contraceptives and income generating activities further help to improve the situation.